The sister's search [large type] - Davis, Susan Page (Homeward Trails, 2023)
"A young woman searches for her missing brother and finds much more awaits her - if she can escape war-torn Texas. Molly Weaver and her widowed mother embark on an arduous journey at the end of the Civil War. They hope to join Molly's brother Andrew on his ranch in Texas. When they arrive, Andrew is missing and squatters threaten the ranch. Can they trust Joe, the stranger who claims to be Andrew's friend? Joe's offer to help may be a godsend - or a snare. And who is the man claiming to be Molly's father? If he's telling the truth, Molly's past is a sham, and she must learn where she really belongs."--